Using the Case Story Method in a Teacher Education Practicum: Affordances and Constraints - Tuluce, Hande Serdar (Edam, 2016)
This case study explored the implementation of the case story method in practicum from the perspective of pre-service English language teachers. Twenty-one senior pre-service teachers were engaged in writing case stories based on their practicum observations and reflecting on those case stories collaboratively. The data obtained from the post-course reflection papers and a focus group interview were analyzed through a thematic analysis. The findings showed that pre-service teachers reported several personal and social affordances of using the case story method in practicum. Compared to the perceived affordances, pre-service teachers emphasized a smaller body of perceived constraints for the implementation of the method with respect to resources and management. In this study, the findings are discussed thoroughly regarding their potential implications for pre-service teacher education.
Keywords: Preservice Teacher Education; Case Story Method; Practicum; Case-Based Pedagogy; Critical Thinking; Reflection; Contexts; Web